2020
DOI: 10.1093/icvts/ivaa150
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival of patients in cardiogenic shock treated by surgically implanted Impella 5+ short-term left ventricular assist device

Abstract: OBJECTIVES Short-term mechanical circulatory support is a life-saving treatment for acute cardiogenic shock (CS). This multicentre study investigates the preoperative predictors of 30-day mortality in CS patients treated with Impella 5.0 and 5.5 short-term left ventricular assist devices. METHODS Data of patients in CS (n = 70) treated with the Impella 5 (n = 63) and 5.5 (n = 7) in 2 centres in Berlin between October 2016 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…report outcomes of patients supported with Impella 5 (63 patients) and 5.5 (seven patients) and concluded that in this cohort, an increased lactate level and cardiopulmonary resuscitation (CPR) before pVAD deployment were predictors of 30 days of survival. 13 In our cohort, only two patients were resuscitated before device placement, both patients presented with ST‐elevation myocardial infarction, and both died after 7 and 30 days on Impella support, respectively. Of note, none of the patients in our cohort had elevated lactate levels at device implant, likely due to other mechanical circulatory support having been in place before pVAD 5.5 (mostly Impella CP or ECMO).…”
Section: Discussionmentioning
confidence: 86%
“…report outcomes of patients supported with Impella 5 (63 patients) and 5.5 (seven patients) and concluded that in this cohort, an increased lactate level and cardiopulmonary resuscitation (CPR) before pVAD deployment were predictors of 30 days of survival. 13 In our cohort, only two patients were resuscitated before device placement, both patients presented with ST‐elevation myocardial infarction, and both died after 7 and 30 days on Impella support, respectively. Of note, none of the patients in our cohort had elevated lactate levels at device implant, likely due to other mechanical circulatory support having been in place before pVAD 5.5 (mostly Impella CP or ECMO).…”
Section: Discussionmentioning
confidence: 86%
“…In the context of CS refractory to inotropic therapy, unloading the LV with MCS can improve native heart function. [5][6][7] Here, we report on a 65-year-old male with profound CS whose heart function improved with Impella 5.5 support. COVID-19 infection was initially managed with Remdesivir but discontinued due to acute kidney injury.…”
Section: Discussionmentioning
confidence: 91%
“…In the context of CS refractory to inotropic therapy, unloading the LV with MCS can improve native heart function 5–7 . Here, we report on a 65‐year‐old male with profound CS whose heart function improved with Impella 5.5 support.…”
Section: Discussionmentioning
confidence: 97%
“…In the absence of ventricular contractility, this can lead to pulmonary hypertension and subsequently to interstitial lung edema 8 . Therefore, in case of isolated left ventricular failure, microaxial left ventricular assist devices such as the Impella (Abiomed Inc.) can be used as an alternative to or in combination with ECLS 9 …”
Section: Introductionmentioning
confidence: 99%